2023
DOI: 10.3892/etm.2023.11976
|View full text |Cite
|
Sign up to set email alerts
|

Study of dietary‑induced progression of psoriasis‑like mice based on gut macrophage polarization

Abstract: The aim of the present study was to investigate the influence of stimulating food (SF), a Traditional Chinese Medicine term for a high protein, high fat diet, on psoriasis exacerbation. It was hypothesized that SF disposed psoriasis-like aggravation might be related to inflammatory pathways induction via gut dysbiosis. In the present study, mice were fed either an SF or normal diet for 4 weeks. In the last week, their back hair was removed to establish psoriasis-like dermatitis by imiquimod. After sacrifice, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, other research has found that stimulation of certain foods (SF) can exacerbate psoriasis, and the expression of Notch and TLR-2/NF-κB p65 signaling pathway proteins in the psoriatic lesions is abnormally reduced, which is related to the severity of the skin lesions. 30 Therefore, changes in the expression of the TLR4/NF-κB signaling pathway also need to be interpreted dialectically.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…However, other research has found that stimulation of certain foods (SF) can exacerbate psoriasis, and the expression of Notch and TLR-2/NF-κB p65 signaling pathway proteins in the psoriatic lesions is abnormally reduced, which is related to the severity of the skin lesions. 30 Therefore, changes in the expression of the TLR4/NF-κB signaling pathway also need to be interpreted dialectically.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Data on the involvement of pro-inflammatory-activated macrophages in other tissues are limited but suggestive. Accordingly, M1 polarized gut macrophages appear to aggravate psoriasiform skin inflammation in imiquimod-treated mice by releasing proinflammatory cytokines [64]. Moreover, imiquimod-treated mice have severe gut dysbiosis accompanied by increased macrophage activation, which has been linked to an increased risk and severity of inflammatory bowel disease [65].…”
Section: Impact Of Macrophage Polarization In Other Tissues On Psoria...mentioning
confidence: 99%
“… Zhang et al (2016) reported that IL-35 can inhibit the inflammatory process in psoriasis by decreasing the M1/M2 macrophage ratio. Zeng et al (2023) demonstrated that polarization of macrophages activates resident immune cells in psoriatic tissues by secreting proinflammatory cytokines and contributes to the exacerbation of psoriasis.…”
Section: Introductionmentioning
confidence: 99%